Technology Management in OrganizationsTechnology Management in Organizations, by GattikerUrs E. Newbury Park, CA: Sage, 1990. - Gattiker, Urs E.; Lawless, Michael W. (Academy of Management Review, 1991)
This article presents a review of the book ?Technology Management in Organizations,? by Urs E. Gattiker.